Reliability of Upper Limb Pin-Prick Stimulation With Electroencephalography: Evoked Potentials, Spectra and Source Localization - Triccas, Lisa Tedesco; Camilleri, Kenneth P.; Tracey, Camilleri; Mansoureh, Fahimi Hnazaee; Benjamin, Wittevrongel; Francesca, Muscat; Leonardo, Boccuni; Dante, Mantini; Geert, Verheyden (Frontiers in Human Neuroscience, 2022)
In order for electroencephalography (EEG) with sensory stimuli measures to be used in research and neurological clinical practice, demonstration of reliability is needed. However, this is rarely examined. Here we studied the test-retest reliability of the EEG latency and amplitude of evoked potentials and spectra as well as identifying the sources during pin-prick stimulation. We recorded EEG in 23 healthy older adults who underwent a protocol of pin-prick stimulation on the dominant and non-dominant hand. EEG was recorded in a second session with rest intervals of 1 week. For EEG electrodes Fz, Cz and Pz peak amplitude, latency and frequency spectra for pin-prick evoked potentials was determined and test-retest reliability was assessed. Substantial reliability ICC scores (0.76-0.79) were identified for evoked potential negative-positive amplitude from the left hand at C4 channel and positive peak latency when stimulating the right hand at Cz channel. Frequency spectra showed an increase of low-frequency (<5 Hz) and also at alpha (6-13Hz) bands extending at 0.31s in the time domain, with excellent reliability between sessions (ICC scores: 0.81-0.98). Sources were identified in the primary somatosensory and motor cortices in relation to the positive using s-LORETA analysis. Measuring the low frequency response from the pin-prick evoked potentials may allow the reliable assessment of central somatosensory impairment in the clinical setting.